2016
DOI: 10.5935/0004-2749.20160005
|View full text |Cite
|
Sign up to set email alerts
|

Mean platelet volume in patients with retinal artery occlusion

Abstract: RESUMO Objetivo: O objetivo deste estudo foi investigar o volume plaquetário médio (MPV) de pacientes com oclusão da artéria da retina (RAO ABSTRACTPurpose: The aim of this study was to investigate the mean platelet volume (MPV) of patients with retinal artery occlusion (RAO). Methods: Thirty-seven patients diagnosed with RAO and 32 control subjects were included in this retrospective study. Retinal artery occlusion was diagnosed on the basis of clinical examination and fundus fluorescein angiography. All part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
0
10
2
Order By: Relevance
“…[12] In their literature review, Şahin et al found that only one study analyzed the relationship between MPV and RAO showing that MPV values were significantly higher in patients with RAO. [13] We could not find any publication that examined the association between NLR, PLR, and RAO. In this study, we compared the NLR and PLR levels in patients with RAO with those of healthy control subjects and examined the relationship between these values.…”
Section: Is a Serious Condition Requiringmentioning
confidence: 93%
“…[12] In their literature review, Şahin et al found that only one study analyzed the relationship between MPV and RAO showing that MPV values were significantly higher in patients with RAO. [13] We could not find any publication that examined the association between NLR, PLR, and RAO. In this study, we compared the NLR and PLR levels in patients with RAO with those of healthy control subjects and examined the relationship between these values.…”
Section: Is a Serious Condition Requiringmentioning
confidence: 93%
“…The exact mechanism of NVG secondary to RVO or DR is multifactorial and remains unknown. It has been shown that platelets play an important role in the pathophysiology of retinal artery occlusion [27], nonarteritic anterior ischemic optic neuropathy [6], ischemic and hemorrhagic stroke [7], and cardiovascular diseases [28]. In this study, 38 patients with NVG secondary to RVO and 47 patients with NVG secondary to DR were studied with regard to platelet parameters and compared to control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a few studies which have evaluated the relationship between MPV and cardiovascular disease [27, 2931]. Sahin M et al [27] reported that patients with retinal artery occlusion had significantly higher MPV values compared with control subjects and was an independent predictor of retinal artery occlusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that increased MPV is an independent risk factor in patients with coronary artery disease [6]. Several recent studies have reported that increased MPV is also associated with supraventricular tachycardia, retinal artery occlusion and adnexal torsion [7][8][9].…”
Section: Introductionmentioning
confidence: 99%